2019
DOI: 10.1098/rstb.2019.0062
|View full text |Cite
|
Sign up to set email alerts
|

Syntax and compositionality in animal communication

Abstract: Syntax has been found in animal communication but only humans appear to have generative, hierarchically structured syntax. How did syntax evolve? I discuss three theories of evolutionary transition from animal to human syntax: computational capacity, structural flexibility and event perception. The computation hypothesis is supported by artificial grammar experiments consistently showing that only humans can learn linear stimulus sequences with an underlying hierarchical structure, a possible by-product of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 55 publications
1
38
0
1
Order By: Relevance
“…Similar phenomena have been observed in putty-nosed monkeys (Cercopithecus nictitans martini) (Arnold & Zuberbühler, 2006a, 2006b. Although these findings show remarkable similarities to some aspects of human syntax in terms of combinatorial and permutational properties, the implications for evolutionary theories of language are far from clear, suggesting that more empirical work is needed (Bolhuis et al, 2018;Townsend et al, 2018;Zuberbühler, 2019b).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar phenomena have been observed in putty-nosed monkeys (Cercopithecus nictitans martini) (Arnold & Zuberbühler, 2006a, 2006b. Although these findings show remarkable similarities to some aspects of human syntax in terms of combinatorial and permutational properties, the implications for evolutionary theories of language are far from clear, suggesting that more empirical work is needed (Bolhuis et al, 2018;Townsend et al, 2018;Zuberbühler, 2019b).…”
Section: Introductionsupporting
confidence: 69%
“…We attribute these findings to the fact that our experimental design consisted of playbacks of song recordings at relatively close distances (about 150 m), which may have been perceived as a social threat by some groups, either territorial or risk of partner defection. Future work is required to test whether these notes are actively used to describe events in hierarchically structured ways (main: predatory threat y/n; subsidiary: social threat y/n), similar to how humans represent natural events as tree structures in both cognition and language (Zuberbühler, 2019b).…”
Section: Singing As Compositional Behaviourmentioning
confidence: 99%
“…In lar gibbons (Hylobates lar), notes were organized differently depending on whether calls were emitted under regular circumstances or when exposed to a predator model [52]. In the case of early morning solo vocalizations emitted by males, the basic units or phrases do not appear to bear any specific meaning [53], despite being highly complex [54], which provides an ideal system to investigate limits on vocal production in different call types emitted under presumably the same context. It may be that similar to gelada vocal sequences and birdsong, that the increasing complexity of male solos provides a more efficient way to deliver the same message [12,55], as opposed to human speech wherein combining different elements brings about different meaning.…”
Section: Introductionmentioning
confidence: 99%
“…This line of research aims at understanding the evolutionary precursors and selective pressures that led from the ability to parse simple forms of compositionality, which has been demonstrated in multiple species, to the human ability to parse fully-fledged syntactic systems of languages (Russell and Townsend 2017). Although much research on this topic is still ongoing, our understanding of the evolution of the human ability for syntax has significantly advanced in the last two decades (Collier et al 2014;Engesser and Townsend 2019;Townsend et al 2018;Zuberbühler 2020). For instance, it has been shown that Campbell's monkeys (Cercopithecus campbelli) add an acoustic modifier (i.e., a sort of affix) to predator-specific alarm calls (Ouattara et al 2009).…”
Section: The Animal Ability To Process Compositional Rules In Vocal Umentioning
confidence: 99%